A generalized inversion formula for the continuous Jacobi transform. (1987) - Zayed, Ahmed I.
Abstract : In this paper we extend the definition of the continuous Jacobi transform to a class of generalized functions and obtain a generalized inversion formula for it. As a by-product of our technique we obtain a necessary and sufficient condition for an analytic functionF ( λ ) inRe λ > 0 to be the continuous Jacobi transform of a generalized function.